Studi Kasus Pemeriksaan Radiologi Colon in Loop Post Colostomy pada Kasus Colitis di Instalasi Radiologi RSUD Banyumas - Nova Erliyani; Amril Mukmin; Retno Wati (JURNAL RISET RUMPUN ILMU KEDOKTERAN, 2025)
Colitis is an inflammatory characterized by thickening of the mucosal wall of the colon. The Colon In Loop examination is one of the diagnostic procedures for colitis, utilizing contrast media to assess the functional condition of the colon. At the Radiology Installation of RSUD (Regional General Hospital) Banyumas, the radiological procedure for Colon In Loop was performed on post-colostomy patients, thus differs from previous studies. This study aims to identify the examination procedure of Colon In Loop at RSUD Banyumas, the rationale for using Anteroposterior (AP) and Lateral projections, and the reason for not performing evacuation before the administration of negative contrast media. This qualitative descriptive study employed a case. The subjects included three radiographers, one radiology nurse, and one radiology specialist. The object of study was the Colon In Loop Post Colostomy examination procedure in colitis cases. Data were collected through observation, interviews, documentation. Data analysis involved data reduction and data presentation. confirmed with theory, and narrative presentation leading to conclusions. Result shows contrast media consisting of 250 grams of barium sulfate dissolved in 1000 ml of water (25% w/v). The examination is performed in stages followed by AP and Lateral projection imaging to evaluate contrast distribution in the colon. Negative contrast media administration is performed without prior evacuation to enhance patient comfort and reduce examination time. When administering negative contrast media, evacuation is not performed before air is introduced. This is done based on the patient's condition, to shorten the examination time, and due to considerations regarding the quality of barium sulfate; thus, evacuation could impair barium adherence to the colon mucosa. In conclusion, AP and lateral projections are considered adequate for establishing a diagnosis of colitis. The omission of evacuation is based on patient condition, time efficiency, and the suboptimal quality of barium. It is recommended to perform evacuation and increase barium concentration to improve adherence to the colon mucosal wall.